Emission of the THz waves from large area mesas of superconducting Bi 2Sr2CaCu2O8+δ by the injection of spin polarized current - Turkoglu, F.; Ozyuzer, O.; Koseoglu, H.; Demirhan, Y.; Preu, Sascha; Malzer, Stefan; Simsek, Yilmaz; Wang, H.B.; Müller, Paul (Physica C-Superconductivity and Its Applications, 2013)
Rectangular Au/Co/Au/BiSrCaCuO (Bi2212) mesa structures with large areas and high thicknesses were fabricated on as-grown Bi2212 single crystals in order to obtain small critical current from as-grown mesas by the injection of spin polarized current and so eliminate the adjustment of doping level for successful THz emission. We have performed c-axis resistance versus temperature (R-T), current-voltage (I-V) characteristics and bolometer measurements. It is the first time that THz emission has been observed from as-grown mesas due to injection of spin polarized current. © 2013 Elsevier Ltd. All rights reserved.
Keywords: THz waves; Intrinsic Josephson junction; Bi2212; Spin polarized current